COVID-19 Monitoring Survey in Poor and Slum Areas of Dhaka and Chittagong : Bangladesh Food Security and Coping Strategies as of Round 2, September 2 - October 2020 - World Bank (World Bank, Washington, DC, 2021)
By September 2020, Dhaka and Chittagong labor markets in Bangladesh showed signs of recovery in employment. Employment recovered faster in Chittagong, reaching pre-COVID-19 levels, while Dhaka remained below pre-COVID-19 employment levels. To track the impacts of the Coronavirus (COVID-19) crisis on labor markets and household coping strategies, a rapid phone survey was implemented on a representative sample of households living in poor and slum areas of Dhaka and Chittagong City Corporations (CCs). This brief, the third in the series, summarizes results from the first and second rounds of the rapid phone survey, conducted from June 10 to July 10, 2020, and from September 2 to October 11, 2020. Ninety-four percent of respondents interviewed in the first survey round were reached in the second round. This brief focuses on how the labor market situation, and how food security and coping strategies evolved between the two rounds.